2000
DOI: 10.1902/annals.2000.5.1.79
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smoking on 3‐Year Clinical Success of Osseointegrated Dental Implants

Abstract: Results suggest that increased implant failures in smokers are not the result of poor healing or osseointegration, but of exposure of peri-implant tissues to tobacco smoke. Data also suggest that detrimental effects may be reduced by: 1) cessation of smoking; 2) the use of preoperative antibiotics; and 3) the use of HA-coated implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 21 publications
9
117
0
12
Order By: Relevance
“…5 These also compromise the healing process 6 and increase the risk of implant failure. [7][8][9][10][11] It has been suggested that smokers are informed of this risk rather than smoking being seen as a contraindication to implant treatment. 12 All three patients had a history of cigarette smoking and two had high alcohol consumption, and they represented high risk cases for developing oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…5 These also compromise the healing process 6 and increase the risk of implant failure. [7][8][9][10][11] It has been suggested that smokers are informed of this risk rather than smoking being seen as a contraindication to implant treatment. 12 All three patients had a history of cigarette smoking and two had high alcohol consumption, and they represented high risk cases for developing oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Bu çalışmanın sonuçlarına göre implant başarısızlık oranları sigara içenlerde sigara içmeyenlere kıyasla daha fazla bulunmuştur ve bu başarısızlık oranını azaltmak için operasyon öncesi antibiyotik kullanımı önerilmiştir (67).…”
Section: İmplant Başarısıunclassified
“…Maksiller implant failleri sigara içenlerde (%10.9) içmeyen veya sigarayı bırakmış bireylere(%6.4) göre daha fazla görülmektedir (67). Güncel bir TARTIŞMA Sigara içimi periodontal hastalığın görülme olasılığı ve hastalığın şiddeti için majör bir risk faktörüdür (80).…”
Section: İmplant Başarısıunclassified
“…In an 8-year long, randomized, prospective clinical trial the researchers concluded that persistent tobacco use following implantation lessened the ability of bone or other periodontal tissues to adapt over time, thus compromising all stages of treatment after fixture uncovering. They suggested smoking cessation for all implant candidates [ 85 ]. Only a few studies conclude that smoking status does not influence implant success [86][87][88].…”
Section: Ementioning
confidence: 99%